Comparative larval morphology of eight species of Hypsiboas Wagler (Amphibia, Anura, Hylidae) from Argentina and Uruguay, with a review of the larvae of this genus - Kolenc, Francisco; Borteiro, Claudio; Alcalde, Leandro; Baldo, Diego; Cardozo, Dario; Faivovich, Julian [UNESP] (Magnolia Press, 2008)
We studied the external and oral cavity morphology of the tadpoles of eight species of Hypsiboas in the H. albopunctatus, H. faber, H. punctatus and H. pulchellus species groups. After a review of the available information about larval external and oral cavity morphology, no character state seems to be synapomorphic for Hypsiboas. The presence of a fleshy projection in the inner margin of the nostrils and rounded vacuities of the anteromedial surface of the choanae (pending the confirmation of the latter in Hyloscirtus and Myersiohyla) seems to be synapomorphic for the tribe Cophomantini, as previously noticed by other authors. Some putative synapomorphies are suggested for some species groups of Hypsiboas, but a denser sampling is needed to study the taxonomic distribution of these character states, in order to determine which clades they may support. The presence of lateral flaps with labial teeth in the oral disc is a variable feature of many species in the H. faber and H. pulchellus groups. A spiracular tube free from the body wall is present in some species, mostly in the H. albopunctatus group, but also in the H. rufitelus, H. faber and H. pulchellus groups. Unique ventrolateral cumules of neuromasts are present in H. faber, and also in some species of other groups of Hypsiboas and of the sister genus Aplastodiscus. Our results highlight the importance of studying the taxonomic distribution of many character states that were sometimes overlooked in tadpole descriptions but seem relevant to test phylogenetic hypothesis.
Keywords: Cophomantini; Hylinae; Hypsiboas andinus; Hypsiboas caingua; Hypsiboas cordobae; Hypsiboas faber; Hypsiboas pulchellus; Hypsiboas punctatus rubrolineatus; Hypsiboas raniceps; Hypsiboas riojanus; larval external morphology; oral papillation; neuromasts